(untitled) (Bulletin of Innovative Research, 2026)
This study looks at how the amount of vocabulary taught before a reading task affects reading comprehension for English for Specific Purposes (ESP) students. The research took place at the “Tashkent Institute of Irrigation and Agricultural Mechanization Engineers” National Research University and included 38 undergraduates from Economics, Aerospace Technology, and Material Science. Using Cognitive Load Theory and the Vocabulary Threshold Hypothesis, the study aimed to find the best amount of vocabulary to teach that helps understanding without causing overload. Students experienced three different pre-teaching levels: low, moderate, and high. The results show that teaching a moderate amount of vocabulary leads to better comprehension than a low amount, while teaching a high amount does not help as much and can cause fatigue. For technical fields like Aerospace and Material Science, focusing on teaching key vocabulary is more effective than teaching every possible word.